2015
DOI: 10.1152/ajplung.00203.2014
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptors and their therapeutic opportunities in diseased lung: Far beyond leukocyte trafficking

Abstract: Chemokine receptors and their chemokine ligands, key mediators of inflammatory and immune cell trafficking, are involved in the regulation of both physiological and pathological processes in the lung. The discovery that chemokine receptors/chemokines, typically expressed by inflammatory and immune cells, are also expressed in structural lung tissue cells suggests their role in mediating the restoration of lung tissue structure and functions. Thus, chemokine receptors/chemokines contribute not only to inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 175 publications
(168 reference statements)
1
27
0
Order By: Relevance
“…5). ECL1i-Dylight 550 also bound lung to macrophages (CD11b hi , CD11c low ) and a very small group of “bright” dendritic cells (CD11b hi , CD11c hi ), consistent with known CCR2 + populations (1, 2). …”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…5). ECL1i-Dylight 550 also bound lung to macrophages (CD11b hi , CD11c low ) and a very small group of “bright” dendritic cells (CD11b hi , CD11c hi ), consistent with known CCR2 + populations (1, 2). …”
Section: Resultssupporting
confidence: 52%
“…Second, CCR2 is elevated in lung cells in ARDS, COPD, experimental asthma and pulmonary fibrosis, as well as common non-pulmonary diseases, including atherosclerosis and malignancy (6,810,17,2528). Third, there is substantial evidence that genetic deletion or pharmacologic inhibition of CCR2 ameliorates disease in animal models leading to industry efforts to develop and trial CCR2 antagonists for respiratory disorders and other disease (2,18,19). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that a CCR2 binding peptide can specifically detect these receptors with PET/CT imaging during lung transplantation-mediated ischemiareperfusion injury in vivo as both a monovalent peptide tracer and a multivalent nanoplatform (25). We recognize that lung stromal cells can express CCR2, which needs to be considered when interpreting CCR2 imaging results (26). However, our findings suggest that any potential contribution of such cells to the CCR2 PET signal in vivo is inconsequential compared with hematopoietic cells.…”
Section: Ischemia-reperfusion Injury-mediated Primary Graft Dysfunctimentioning
confidence: 78%